Research on the Technologies of Food Extraction, Pressing and Extrusion - Christianne E. C. Rodrigues; Maria Carolina Capellini; Daniel Gonçalves (Foods)
This Editorial refers to the Special Issue “Research on the Technologies of Food Extraction, Pressing and Extrusion”, which highlights new opportunities and challenges in advancing the development of new food products and increasing processing efficiency [...]